Adsorption mechanism of extracellular polymeric substances from two bacteria on Ultisol and Alfisol. (June 2018) - Ren, Li-ying; Hong, Zhi-neng; Qian, Wei; Li, Jiu-yu; Xu, Ren-kou
Abstract: The primary objective of this study was to identify the capacity and mechanism of extracellular polymeric substance (EPS) adsorption on soil colloids of Alfisol and Ultisol at different pH and ionic strengths. Two kinds of EPS were extracted from Bacillus subtilis and Pseudomonas fluorescens by centrifugation, and their adsorption on Ultisol and Alfisol was investigated using a batch adsorption experiment and attenuated total reflectance–Fourier transform infrared spectroscopy (ATR-FTIR). The average diameter of EPS from B. subtilis and P. fluorescens was 1825 and 1288 nm, respectively, and both the EPS were negatively charged. The zeta potentials of the two EPS became more negative with increasing solution pH from 3 to 8 and less negative with increasing ionic strength from 0 to 80 mM. The maximum adsorption capacity of EPS-C and EPS-N on Alfisol was higher than that on Ultisol, whereas the maximum adsorption capacity of EPS-P on Alfisol was lower than that on Ultisol. The adsorption of EPS-C, EPS-N, and EPS-P of both the EPS on Ultisol and Alfisol decreased with increasing solution pH from 3 to 8. Adsorption of EPS-C, EPS-N, and EPS-P of both the EPS on Alfisol significantly increased with increasing ionic strength from 0 to 10 mM, whereas it remained constant, slightly increased, or reduced, when the ionic strength was increased from 10 to 80 mM. The adsorption of EPS-C, EPS-N, and EPS-P on Ultisol slightly increased with increasing ionic strength from 0 to 80 mM. Saturation coverage determined by ATR-FTIR showed that adsorption of whole EPS on Ultisol was higher than that on Alfisol at pH 6 after 60 min. Thus, electrostatic force between EPS and soil colloids played an important role in EPS adsorption. Besides, proteins and phosphate groups in EPS also contributed to EPS adsorption on soil colloids. Graphical abstract: Image 1 Highlights: Ultisol had lower sorption capacity for EPS-C, -N but higher for EPS-P than Alfisol. Electrostatic force played an important role in EPS adsorption. Protein and phosphate groups also contributed to EPS adsorption. ATR-FTIR can be used to examine kinetics of EPS adsorption on soil colloids. Components of soil colloids affected adsorption of EPS-C, -N and -P. Abstract : Electrostatic force between EPS and soil colloids played an important role in EPS adsorption. Besides, proteins and phosphate groups in EPS also contributed to EPS adsorption on soil colloids.